Chronic cholesterol depletion increases F-actin levels and induces cytoskeletal reorganization via a dual mechanism - Parijat Sarkar; G. Aditya Kumar; Sandeep Shrivastava; Amitabha Chattopadhyay (Journal of Lipid Research, 2022)
Previous work from us and others has suggested that cholesterol is an important lipid in the context of the organization of the actin cytoskeleton. However, reorganization of the actin cytoskeleton upon modulation of membrane cholesterol is rarely addressed in the literature. In this work, we explored the signaling crosstalk between cholesterol and the actin cytoskeleton by using a high-resolution confocal microscopic approach to quantitatively measure changes in F-actin content upon cholesterol depletion. Our results show that F-actin content significantly increases upon chronic cholesterol depletion, but not during acute cholesterol depletion. In addition, utilizing inhibitors targeting the cholesterol biosynthetic pathway at different steps, we show that reorganization of the actin cytoskeleton could occur due to the synergistic effect of multiple pathways, including prenylated Rho GTPases and availability of membrane phosphatidylinositol 4,5-bisphosphate. These results constitute one of the first comprehensive dissections of the mechanistic basis underlying the interplay between cellular actin levels and cholesterol biosynthesis. We envision these results will be relevant for future understating of the remodeling of the actin cytoskeleton in pathological conditions with altered cholesterol.